Hubungan antara Iklim Sekolah dan Subjective Well-Being Siswa SMP Korban Perundungan Siber di Kota Bandung - Silvia Febriyani Dwi Maharani; Ihsana Sabriani Borualogo (UNISBA Press, 2022)
Abstract. This research aims to determine the components of school climate which can affect junior high school students' SWB, especially for those who have been the victims of cyber-bullying and live in Bandung. The data are collected online by using Google Forms through convenience sampling technique. The participants are junior high school students who have been the victims of cyber-bullying, ranging from age 12 – 16 years old (N = 537; 58.5% female; 41.5% male). The perceptions of school climate are measured with a measuring instrument from Children's World, while the SWB is measured with Children's Worlds Subjective Well-Being Scale 5 Items version (CW-SWBS5), and the categorization of the students who have been the victims of cyber-bullying used an instrument from Patchin and Hinduja. The data are analyzed with linear regression analysis so as to examine school climate components' contribution for the SWB of the victims of cyber-bullying. Descriptive statistic ANOVA is used to test the difference in the mean of SWB. The results show that school climate components have a 17.5% relationship with the SWB of junior high school students who have been the victims of cyber-bullying. The school climate components that contribute significantly to the SWB of these victims are the perception on friends who are willing to help when they get into trouble (ꞵ = .152; p < .01) and the perception of class fights (ꞵ = -.146; p < .01). Schools should ensure that their climate is conducive to avoiding violence between students, and teachers should pay attention to the relationship between students so that it is known who their close friends are who can help or support when facing problems. Abstrak. Penelitian ini bertujuan untuk mengetahui komponen iklim sekolah yang berkontribusi pada SWB siswa SMP korban perundungan siber di Kota Bandung. Pengambilan data dilakukan secara online menggunakan Google Formulir dengan teknik convenience sampling. Partisipan penelitian yaitu siswa SMP yang pernah menjadi korban perundungan siber berusia 12 – 16 tahun (N = 537; 58.5% perempuan; 41.5% laki-laki). Persepsi iklim sekolah diukur menggunakan alat ukur iklim sekolah dari Children’s World, SWB diukur menggunakan Children’s Worlds Subjective Well-Being Scale 5 Items (CW-SWBS5), dan kategorisasi siswa yang menjadi korban perundungan siber diukur menggunakan alat ukur perundungan siber dari Patchin dan Hinduja. Data dianalisis menggunakan analisis regresi linear untuk menguji kontribusi komponen iklim sekolah terhadap SWB korban perundungan siber. Statistika deskriptif ANOVA digunakan untuk menguji perbedaan nilai rerata SWB. Hasil penelitian menunjukkan bahwa komponen iklim sekolah memberikan kontribusi terhadap SWB siswa SMP korban perundungan siber sebesar 17.5%. Terdapat komponen iklim sekolah yang memberikan kontribusi secara signifikan terhadap SWB korban perundungan siber, yaitu persepsi mengenai teman yang menolong ketika mendapatkan masalah (ꞵ = .152; p < .01), dan persepsi mengenai pertengkaran di kelas (ꞵ = -.146; p < .01). Sekolah perlu memastikan iklimnya bersifat kondusif agar terhindar dari kekerasan antar siswa, serta guru perlu memperhatikan hubungan antar siswa agar diketahui siapa teman terdekat mereka yang dapat memberikan bantuan ataupun dukungan ketika menghadapi permasalahan.